2018
DOI: 10.1007/978-1-4939-7598-3_32
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Reactive Oxygen Species (ROS) and Mitochondrial ROS in AMPK Knockout Mice Blood Vessels

Abstract: Reactive oxygen species (ROS) are a group of unstable and highly reactive molecules or free radicals typically generated as by-products of cellular processes involving molecular oxygen. In vascular cells, the excessive ROS generation results in the initiation and progression of cardiovascular diseases (CVD). Therefore, a dynamic, robust, and accurate ROS detection method in the blood vessels is essential for pathophysiological research studies of the cardiovascular system.In this chapter, we describe a fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 18 publications
1
59
0
Order By: Relevance
“…The higher ROS content, assessed in IF 1 -silenced cells compared to controls in both normoxia and hypoxia, prompted us to investigate whether these changes were associated with a different rate of mitochondrial superoxide anion production. To this aim, we performed experiments by using the specific and sensitive mitochondria-targeted superoxide probe MitoSOX Red [ 27 ]. Loading cells with the dye revealed a mild but significant increase of the superoxide anion production in IF 1 -silenced cells compared to controls, when cells were exposed to either normoxia (about 61 and 50% top right quadrant cells in IF 1 -silenced and control cells, respectively) or hypoxia (about 43 and 33% top right quadrant cells in IF 1 silenced and control cells, respectively) for 24 h ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher ROS content, assessed in IF 1 -silenced cells compared to controls in both normoxia and hypoxia, prompted us to investigate whether these changes were associated with a different rate of mitochondrial superoxide anion production. To this aim, we performed experiments by using the specific and sensitive mitochondria-targeted superoxide probe MitoSOX Red [ 27 ]. Loading cells with the dye revealed a mild but significant increase of the superoxide anion production in IF 1 -silenced cells compared to controls, when cells were exposed to either normoxia (about 61 and 50% top right quadrant cells in IF 1 -silenced and control cells, respectively) or hypoxia (about 43 and 33% top right quadrant cells in IF 1 silenced and control cells, respectively) for 24 h ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry determination of ROS, the most contributors to total cellular reactive oxidant species, and superoxide anion was performed using a MUSE cytometer (Merk Millipore, Darmstadt, Germany) after loading the cells with either 5 μM CellROX Orange or 5 μM MitoSOX Red [ 25 , 26 , 27 ], respectively. The cells were incubated with each dye for 30 min at 37 °C under both normoxia and hypoxia (0.5% O 2 ) and wells were then washed with HBSS to remove any remaining unincorporated dye.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a normal balance of ROS is essential for cellular functions; however, once the level of ROS surpasses the standard concentration, cellular damage will result, leading finally to apoptosis and cellular death [54,55]. Therefore, an accurate and potent detection method of ROS is crucial for cardiovascular system studies [56], but ROS measurement with high accuracy is still challenging because of ROS' short half-life [57]. Griendling et al listed all measurement approaches of ROS in detail [58].…”
Section: Measurements Of Ros In Circulating Cellsmentioning
confidence: 99%
“…The most widely used method to quantify cellular O 2 − in mammalian cells is based on DHE staining. MitoSOX or HPLC are currently being used for mitochondrial O 2 − detection, although one major limitation of the latter is the inability to distinguish the specific cells contributing to ROS production in response to pathological stimuli [42]. In our study, we found an increase in superoxide anion (O 2 − ) content in the aorta of rats treated with Su compared with the control group.…”
Section: Discussionmentioning
confidence: 59%